Study of the Transition from Non-Injection to Injection in Heroin Users - Mosaieb Yarmohammadi Vasel; Fatemeh Ghanadi (پزشکی بالینی ابن سینا, 2010)
Introduction & Objectives: The goal of our study was to elucidate the time and factors influencing the transition from non-injection to injection among male heroin users. Materials & Methods: In this retrospective cohort study conducted in Iran from April to August 2007, the data was obtained from the subjects who had never injected heroin at study entry. The total population included 7743 (402 women and 7341 men) substance dependents in Iran. In this study we enrolled 1641 non-injecting male heroin users. The data was collected through Inventory Rapid Situation Assessment (RSA). Results: The results revealed that among the 1641 never injectors, 591 had initiated injection (The incidence of initiation into injection was 36% after 6.5 years). Independent predictors of transition into injection among non-injecting heroin users were being single, unemployment, attending injecting friends’ gatherings , age at first heroin use(early adolescent drug use). Conclusion: The study suggests that several factors increase the risk of injecting drugs among heroin users. Interventions to prevent injecting should identify risk factors associated with the transition from heroin sniffing to heroin injection